Hypoxia-Driven Immunosuppressive Metabolites in the Tumor Microenvironment: New Approaches for Combinational Immunotherapy - Li, Yiliang; Patel, Sapna Pradyuman; Roszik, Jason; Qin, Yong (Frontiers in Immunology, 2018)
Hypoxia is not only a prominent contributor to the heterogeneity of solid tumors but also a crucial stressor in the microenvironment to drive adaptations for tumors to evade immunosurveillance. Herein, we discuss the potential role of hypoxia within the microenvironment contributing to immune resistance and immune suppression of tumor cells. We outline recent discoveries of hypoxia-driven adaptive mechanisms that diminish immune cell response via skewing the expression of important immune checkpoint molecules (e.g. CD47, PD-L1, and HLA-G), altered metabolism and metabolites, and pH regulation. Importantly, inhibition of hypoxic stress-relevant pathways can collectively enhance T-cell mediated tumor cell killing. Furthermore, we discuss how manipulation of hypoxia stress may pose a promising new strategy for a combinational therapeutic intervention to enhance immunotherapy of solid tumors.